CNC table based compensation of inter-axis and linear axis scale gain errors for a five-axis machine tool from symbolic variational kinematics. Issue 1 (2021) - Esmaeili, Sareh M.; Mayer, J.R.R.
Abstract: A compensation lookup tables (LUTs) scheme is programmed using a CNC's indigenous LUTs capability to virtually correct geometric error parameters of a five-axis machine tool. Using variational kinematics, the geometric errors are forward propagated to the tool tip and the required axis command corrections are obtained in closed form by inverse kinematics. 40 lookup tables and multiplication and summation functionalities compensate ten inter-axis errors and three linear positioning gain errors. Validation tests on a wCAYFXZt topology machine with a 45° angle between the C- and A-axis show significant reductions in dominant geometric errors and a 79% improvement in volumetric errors.